Cutaneous neurofibromas: Current clinical and pathologic issues. (10th July 2018) - Ortonne, Nicolas; Wolkenstein, Pierre; Blakeley, Jaishri O.; Korf, Bruce; Plotkin, Scott R.; Riccardi, Vincent M.; Miller, Douglas C.; Huson, Susan; Peltonen, Juha; Rosenberg, Andrew; Carroll, Steven L.; Verma, Sharad K.; et al.
Abstract : Objective: To present the current terminology and natural history of neurofibromatosis 1 (NF1) cutaneous neurofibromas (cNF). Methods: NF1 experts from various research and clinical backgrounds reviewed the terms currently in use for cNF as well as the clinical, histologic, and radiographic features of these tumors using published and unpublished data. Results: Neurofibromas develop within nerves, soft tissue, and skin. The primary distinction between cNF and other neurofibromas is that cNF are limited to the skin whereas other neurofibromas may involve the skin, but are not limited to the skin. There are important cellular, molecular, histologic, and clinical features of cNF. Each of these factors is discussed in consideration of a clinicopathologic framework for cNF. Conclusion: The development of effective therapies for cNF requires formulation of diagnostic criteria that encompass the clinical and histologic features of these tumors. However, there are several areas of overlap between cNF and other neurofibromas that make distinctions between cutaneous and other neurofibromas more difficult, requiring careful deliberation with input across the multiple disciplines that encounter these tumors and ultimately, prospective validation. The ultimate goal of this work is to facilitate accurate diagnosis and meaningful therapeutics for cNF.